Collaborative Downloading for Multi-homed Wireless Devices - Ananthanarayanan, Ganesh; Padmanabhan, Venkat; Thekkath, Chandu; Ravindranath, Lenin (IEEE HotMobile, 2007)
Mobile devices are increasingly equipped with multiple network interfaces: Wireless Local Area Network (WLAN) interfaces for local connectivity and Wireless Wide Area Network (WWAN) interfaces for wide-area connectivity. The WWAN typically provides much wider coverage but much lower speeds than the WLAN. To address this dichotomy, we consider collaborative downloading among mobile devices in close proximity. We demonstrate the potential beneﬁts of such an approach and discuss the many challenges to realizing it in practice: incentivizing cooperation by adequately compensating nodes, effecting such cooperation via an efﬁcient protocol, and facilitating it with a suitable user interface. We present our current thinking on these as we design a collaborative downloading system called COMBINE.